2008
DOI: 10.14203/mri.v22i0.432
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Indo-West Pacific Palicidae (Crustacea : Decapoda) With Descriptions of Two New Subfamilies, Four New Genera and Six New Species

Abstract: Twelve species of Crustacea of the family Palicidae were collected from Indonesian waters. Together with two species from the Philippines and type specimens of Crossotonotus compressipes A. Milne Edwards, 18 73, are studied and Manella spinipes is used for comparison. Two new subfamilies, four new genera, and six new species are described and the type of Crossotonotus compressipes has been designated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The family Palicidae, formerly including two subfamilies (Moosa & Serène 1981;Castro 2000;Ng et al 2008), is now regarded as consisting of two families, Palicidae Bouvier, 1898, and Crossotonotidae Moosa & Serène, 1981, following Guinot et al (2013 who showed that the two subfamilies should be recognized as the full families diagnosed by their respective sternum, abdomens, and male pleopod structure.…”
Section: Introductionmentioning
confidence: 99%
“…The family Palicidae, formerly including two subfamilies (Moosa & Serène 1981;Castro 2000;Ng et al 2008), is now regarded as consisting of two families, Palicidae Bouvier, 1898, and Crossotonotidae Moosa & Serène, 1981, following Guinot et al (2013 who showed that the two subfamilies should be recognized as the full families diagnosed by their respective sternum, abdomens, and male pleopod structure.…”
Section: Introductionmentioning
confidence: 99%
“…Five specimens from fi ve stations in the Philippines (ZRC 2008(ZRC .0954, 2008(ZRC .1078(ZRC , 2008(ZRC .1081(ZRC , 2008(ZRC .1083(ZRC , 2008(ZRC .1085) are close to Parapalicus piruensis Moosa &Serène, 1981, known from Indonesia, New Caledonia andFiji (Castro 2000: table 6, fi g. 58). All specimens share some characters of the general morphology of the carapace and ambulatory legs with P. piruensis: fi nely granular carapace; triangular and acute-tipped anterolateral teeth; suborbital borders each with a wide, V-shaped gap between the inner and outer suborbital lobes, the outer lobe much smaller than the inner lobe; and short ambulatory legs (Moosa & Serène 1981: fi g. 2b, pl.…”
Section: Remarksmentioning
confidence: 99%
“…No other palicoid crabs had been previously listed from Tonga. Th e 2002 BENTHAUS expedition to the Austral Is, French Polynesia resulted in the discovery of an undescribed species of Neopalicus Moosa & Serène, 1981. Th e material obtained by the PANGLAO 2004 and PANGLAO 2005 expeditions and by earlier collections from Panglao I. resulted in four species of palicids and three species of crossotonotids being recorded for the fi rst time from the Philippines.…”
Section: Introductionmentioning
confidence: 99%
“…Remarks. The superfamily Palicoidea Bouvier, 1898 includes the families Palicidae Bouvier, 1898 and Crossotonotidae Moosa and Serène, 1981. While the fifth pairs of pereopods (P5) of the members of the family Palicidae are greatly reduced and slender as the P5 of the dorippid crabs, those of Crossotonotus spinipes (De Man, 1888) belonging to the family Crossotonotidae are identical in shape to the remaining pereopods (P2-P4) (Castro, 2000;Ng et al, 2008).…”
Section: Systematic Accountsmentioning
confidence: 99%
“…However, it is rarely captured in large numbers and almost nothing is known of their biology or life histories (Davie, 2002). The genus Crossotonotus A. Milne Edwards, 1873 including this species consists of four species worldwide: Crossotonotus ceramensis (Moosa and Serène, 1981), C. compressipes A. Milne-Edwards, 1873, C. lophocheir Castro, 2000, and C. spinipes (De Man, 1888 (Ng et al, 2008).…”
Section: Introductionmentioning
confidence: 99%